2023
DOI: 10.3390/s23187774
|View full text |Cite
|
Sign up to set email alerts
|

Image Reconstruction Using Supervised Learning in Wearable Electrical Impedance Tomography of the Thorax

Mikhail Ivanenko,
Waldemar T. Smolik,
Damian Wanta
et al.

Abstract: Electrical impedance tomography (EIT) is a non-invasive technique for visualizing the internal structure of a human body. Capacitively coupled electrical impedance tomography (CCEIT) is a new contactless EIT technique that can potentially be used as a wearable device. Recent studies have shown that a machine learning-based approach is very promising for EIT image reconstruction. Most of the studies concern models containing up to 22 electrodes and focus on using different artificial neural network models, from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 69 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…Comparing the quality measures obtained on the brain image dataset with the results obtained on the thorax dataset [ 15 ], it is essential to notice that brain reconstruction appears to be a more complicated task for the neural network. This was expected since the brain is surrounded by a skull with a much lower conductivity and electrical permittivity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparing the quality measures obtained on the brain image dataset with the results obtained on the thorax dataset [ 15 ], it is essential to notice that brain reconstruction appears to be a more complicated task for the neural network. This was expected since the brain is surrounded by a skull with a much lower conductivity and electrical permittivity.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work [ 15 ] showed that modified cGAN-based neural network architecture inspired by the Pix2Pix approach [ 50 ] is very promising for electrical tomography image reconstruction. Previously, this network was trained on the imaginary component of normalized measurement data obtained by simulating measurements for an empty sensor and the sensor filled with high-conductivity material.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both monofrequency and Multifrequency Electrical Impedance Tomography techniques have been developed since the 1980s and serve various applications in medicine. These include monitoring and imaging in cases of hospitalization due to SARS-CoV-2 [1][2][3], acute respiratory distress syndrome (SARS) [4], lung pathologies using artificial intelligence [5], lung cancer [6], lung embolism [7], breast cancer imaging [8,9], prostate tumors [10], tumor detection [11], and emphysema [12]. MfEIT has also been used in conjunction with other imaging modalities, such as magnetic resonance imaging, magnetic induction tomography, and computed tomography, to enhance the speed and quality of image acquisition.…”
Section: Introductionmentioning
confidence: 99%